A survey of cancer and occupation in young and middle aged men. I. Cancers of the respiratory tract. - Coggon, D (1986)
In a search for clues to previously industrial carcinogens the occupational and smoking histories of young and middle aged men with different types of cancer were compared. The study population comprised men aged 18-54 and resident in the counties of Cleveland, Humberside, and Cheshire (including the Wirral). From hospital and cancer registration records 2942 members of the study population in whom cancers were diagnosed during the period 1975-80 were identified retrospectively. The occupational and smoking histories of these patients were sought by a postal questionnaire addressed either to the patients themselves or, if they had died, to their next of kin. The overall response rate to the questionnaire was 52.1%. Additionally, limited occupational information was obtained for 89% of cases from their hospital notes. Analysis of these data suggests that no serious bias arose as a consequence of the incomplete response to the questionnaire. This paper concentrates on the results for cancers of the respiratory tract and mesothelioma. Mesothelioma was found to cluster in laggers, electricians, and shipyard workers, and nasal carcinoma in woodworkers. Carcinomas of the larynx and of the bronchus were examined by formal statistical techniques, each being compared with a control group made up of all other cancers combined. Several interesting occupational and industrial associations were shown, in particular, an excess of bronchial carcinoma in the leather industry (RR = 2.6, CI 1.2-6.0), in building labourers (RR = 1.7, CI 1.0-2.9) and other construction workers (RR = 1.8, CI 1.0-3.0), in bakers and pastry cooks (RR = 3.6, CI 1.3-10.4). and in cooks (RR = 2.5, CI 1.2-5.1). In addition, a small cluster of lung tumours was observed in men who had worked as dental mechanics.